Higher Education in the society of virtual capitalism and postmodern individualisation: implications for the production and disclosure of knowledge in the Education field (Práxis Educativa, 2010)
In this paper, I discuss the contemporary scenario of higher education and examine the historical circumstances that have contributed to organising it the way it is today, i.e., characterised by the world domination of virtual capital and by the discourse of abstract individualisation. In order to pursue this task, I make use of ideas from Kurz, Lukács, Duarte and Moraes that, in the light of historical materialism, provide a substantial theoretical and methodological basis for understanding such reality, its history and complex relations, according to an ontological perspective. Following this view, I try both to investigate the effects of researchers and professors from the Education field joining the spirit of the epoch and to suggest ways to counteract this spirit by using criticism, aiming to make plain that presently knowledge is a commodity within the society of virtual capitalism and postmodern individualisation. Keywords: Higher education. Knowledge. Commodity.